1983
DOI: 10.1038/bjc.1983.181
|View full text |Cite
|
Sign up to set email alerts
|

Alphafoetoprotein uptake by cloned cell lines derived from a nickel-induced rat rhabdomyosarcoma

Abstract: Summary Rat, mouse, pig and chicken alphafoetoproteins (AFP), rat serum albumin and egg albumin, or their fluoresceinated conjugates were added to cultures of several cloned cell lines isolated from a nickelinduced rat rhabdomyosarcoma. The intracellular uptake of assayed proteins was revealed by the indirect immunoperoxidase technique and/or by direct fluorescence microscopy. All (Trojan & Uriel, 1979;Uriel et al., 1982) and birds (Moro & Uriel, 1981). We have subsequently demonstrated that neuron-like ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 14 publications
2
25
0
Order By: Relevance
“…AFP and albumin were mainly localized in uncoated vesicles near the cell surface. Previous work centered on the study of AFP binding and uptake has been performed in highly specialized cells, including different lymphoid and leukemia cell lines [27-29, 31, 36, 38-40], the MCF-7 breast cancer cell line [18], skeletal muscle cells [14] or rhabdomyosarcoma cell lines [17,19,30]. This is the first study using hepatoma cells.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…AFP and albumin were mainly localized in uncoated vesicles near the cell surface. Previous work centered on the study of AFP binding and uptake has been performed in highly specialized cells, including different lymphoid and leukemia cell lines [27-29, 31, 36, 38-40], the MCF-7 breast cancer cell line [18], skeletal muscle cells [14] or rhabdomyosarcoma cell lines [17,19,30]. This is the first study using hepatoma cells.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have shown that the ability to internalize AFP, which is characteristic of developing cells [14][15][16], may reappear in neoplastic cells [17][18][19]. The existence of an albumin receptor has been postulated in different cell types [20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Fluorescein conjugates were prepared by incubating proteins with fluorescein isothiocyanate (FITC; Sigma) as reported elsewhere (9). The FITC/protein molar ratio ranged from 1.5 to 3 for all proteins except a2M, which was -10.…”
Section: Methodsmentioning
confidence: 99%
“…The intracellular presence of AFP in fetal tissues other than the liver and the yolk sac is due to active uptake of the protein (5,6) and not local synthesis (3,7). It has also been shown that the ability to internalize AFP may be shared by neoplastic cells of different origin, such as spontaneous mammary carcinomas growing in the mouse (8), as well as in two cultured cell lines derived from a rat rhabdomyosarcoma (9) and a human breast carcinoma (10). Preliminary morphological observations of AFP uptake by these cultured cells suggested the existence of a receptor-mediated mechanism.…”
mentioning
confidence: 99%
“…In vitro and in vivo studies showed that malignant cells regain the ability to take up afp via a receptor that would be present in undifferentiated cells of either embryonic or tumour origin [10][11][12][13][14][15] , but mostly absent in normal adult cells. The existence of such a receptor for afp (recaf) was then demonstrated and functionally characterized in several cell lines [16][17][18] .…”
Section: Introductionmentioning
confidence: 99%